PENGALAMAN ANAK USIA SEKOLAH TERHADAP KEBIASAAN MAKAN KELUARGA BERDASARKAN LETAK GEOGRAFIS: PERSPEKTIF KEPERAWATAN KOMUNITAS - Nurharlinah; Ari Athiutama; Uswatun Hasanah (Jurnal Keperawatan Abdurrab, 2026)
Family eating habits significantly influence the nutritional intake of school-age children. In rural villages like Pemulutan Village, Ogan Ilir Regency, geographic location and local food availability contribute to family eating patterns. Understanding children's experiences is crucial to support family-based community nursing interventions. This study aims to explore school-age children's experiences related to family eating habits, considering the influence of the geographic location of Pemulutan Village, Ogan Ilir. This study employed a qualitative research method with a phenomenological approach. Participants were eight children aged 6–12 years living in Pemulutan Village, selected through purposive sampling. Data were collected using in-depth semi-structured interviews and analyzed using thematic analysis. Four main themes emerged: (1) river fish as the family's staple food, (2) limited food variety due to rural location, (3) the role of parents in determining food choices based on local availability, and (4) the meaning of eating together as a form of family adaptation to the environment. This study concludes that the geographic location of Pemulutan Village influences the family eating habits of school-age children. Community nurses can develop family-based nutrition education and utilize local foods to support child growth and development.